Modeling Breast Ultrasound on the Applicability of Commonly Made Approximations - TASKIN, Ulas; OZMEN, Neslihan; GEMMEKE, Hartmut; van Dongen, Koen W.A. (Archives of Acoustics, 2018)
To design breast ultrasound scanning systems or to test new imaging methods, various computer models are used to simulate the acoustic wave field propagation through a breast. The computer models vary in complexity depending on the applied approximations. The objective of this paper is to investigate how the applied approximations affect the resulting wave field. In particular, we investigate the importance of taking three-dimensional (3-D) spatial variations in the compressibility, volume density of mass, and attenuation into account. In addition, we compare four 3-D solution methods: a full-wave method, a Born approximation method, a parabolic approximation method, and a ray-based method. Results show that, for frequencies below 1 MHz, the amplitude of the fields scattering off the compressibility or density contrasts are at least 24 dB higher than the amplitude of the fields scattering off the attenuation contrasts. The results also show that considering only speed of sound as a contrast is a valid approximation. In addition, it is shown that the pressure field modeled with the full-wave method is more accurate than the fields modeled using the other three methods. Finally, the accuracy of the full-wave method is location independent whereas the accuracy of the other methods strongly depends on the point of observation.